Insight into the regulatory mechanism of dynamic chromatin 3D interactions during cardiomyocyte differentiation in human - Hui Liu; Yingying Ma; Jiaxin Yu; Xiang Chen; Shuyuan Wang; Yijie Jia; Na Ding; Xiaoyan Jin; Yunpeng Zhang; Juan Xu; Xia Li (Elsevier, 2023)
Cardiogenesis is an extremely complicated process involved with DNA regulatory elements, and trans factors regulate gene expression pattern spatiotemporally. Enhancers, as the well-known DNA elements, activate target gene expression by transcription factors (TFs) occupied to organize dynamic three-dimensional (3D) interactions, which when affected or interrupted might cause heart defects or diseases. In this study, we integrated transcriptome, 3D genome, and regulatome to reorganize the global 3D genome in cardiomyogenesis, showing a gradually decreased trend of both chromatin interactions and topological associating domains (TADs) during cardiomyocyte differentiation. And almost all of the chromatin interactions occurred within the same or between adjacent TADs involved with enhancers, indicating that dynamical rewiring of enhancer-related chromatin interactions in the continuous expansive TADs is closely correlated to cardiogenesis. Moreover, we found stage-specific interactions activate stage-specific expression to be involved within corresponding biological functions, and the stage-specific combined regulations of enhancers and binding TFs form connected networks to control stage-specific expression and biological processes, which promote cardiomyocyte differentiation. Finally, we identified markers based on regulatory networks, which might drive cardiac development. This study demonstrates the power of enhancer interactome combined with active TFs to reveal insights into transcriptional regulatory networks during cardiomyogenesis.